Chernobyl/Chornobyl Imagery in Popular Music: Voices From Ukraine: Voices From Ukraine - Ostapchuk, Tetiana (Border Crossing, 2024)
The Chornobyl disaster took on planetary significance, but Ukrainian voices were marginalized for many years by more powerful, dominant discourses. This paper explores how Chornobyl trauma has been re-presented by Ukrainian popular music artivists between 2000 and 2020. The case study focuses on narrating, visualizing, and vocalizing strategies by Andriy Kuzmenko, Nata Zhyzhchenko, and Valeriy Korshunov. The author aims to show how these projects were inspired by the Anthropocene ideas. The paper demonstrates how the Ukrainian artists crossed territorial and cultural borders while concurrently transforming the image of the Chornobyl Zone from being a bordered alienated land into a boderscape of interaction between diverse agents.